Pick Your Own Rubbish: An Analysis of Target Group Compliance in Public Policy Implementation - RACHMAWATI, TUTIK; RINJANY, DHIA KALILA (Universitas Muhammadiyah Yogyakarta, 2016)
The purpose of this research is to analyse the implementation of Local Govern-ment Act Bandung Municipality Number 11/2005 about Orderliness, Cleanliness and Fineness of Bandung City (Ketertiban, Kebersihan dan Keindahan). The study focuses on a target-group compliance perspective. By analyzing the level of pub-lic compliance, this research will contribute to the understanding of factors con-tributing to the success of public policy implementation. An analysis of the non-compliance behaviours of the target group is based on three concepts: (1) Fac-tors affecting the level of compliance by Weaver; 2) organizational compliance factors for Economic Co-operation and Development/OECD; and 3) The failure of policy implementation (Patton and Sawicki, 1993)). An early observation showedthat the low level of public compliance were caused by several factors such as 1) problem of reward and punishment; (2) low level of law enforcement by internal investigator orÂ Petugas Satuan Polisi Pamong Praja, 3) The lack of autonomy within the public to comply the legal regulation;4) the lack of information about the policy and its implementation and (5) the value hold by the society that cleanliness is not the society responsible, that it is acceptable to throw any waste anywhere, and 6) The lack of resource to enable the society to comply with the policy. This research evaluates whether such factors also present among the tar-get group of this policy